Penicillium Species Isolated From Cocoa, Coffee Beans, and Dried Cassava in Yogyakarta Indonesia and Their Ochratoxin Production - Mona Nur Moulia; Sigit Setyabudi; Baharuddin Salleh; Endang S. Rahayu (Indonesian Food and Nutrition Progress, 2014)
The presence of Penicillium in cocoa and coffee beans, and dried cassava are detrimental due to its ability in ochratoxin A (OTA) production which carcinogenic and mutagenic to human. Objectives of this study were to isolate and identify Penicillium from cocoa, coffee beans and dried cassava in Yogyakarta by morphological and molecular characteristics, as well as to observe the ability of these isolates in OTA production on Yeast Extract Sucrose Agar (YES) medium. In this study, morphological characteristics were mainly based on the growth of isolates on identification media, while molecular characteristics were based on the similarity of PCR products using ITS4 and ITS5 as primers. OTA was detected by ELISA and UPLC methods. The result showed that 15 of 16 representative isolates obtained during this study were identified as Penicillium citrinum, one of the representative isolate from cocoa beans was identified as Penicillium paneum. Surprisingly, 13 among 15 of the obtained P. citrinum isolates from cocoa and coffee beans were positive in the production of OTA in YES medium, at the concentration of 4.64 to 25.26 µg/g media, while OTA was not detected in YES grown media by P. paneum and two isolates of P. citrinum from dried cassava. Conclusion of this study, the most found species Penicillium in cocoa and coffee beans were belong to P. citrinum which likely have a capability in the production of OTA.